Aetna : investing in diversity - Cascio, Wayne F. ([London] : SAGE, 2016)
Raymond Marcos, chief diversity officer at Aetna, is preparing to make a presentation to the company's board of directors at its mid-December meeting. In a deteriorating economic environment that seems to be global in its reach, the board is looking to cut expenses in any way possible. To do that, it is reviewing every major company business initiative. Diversity is one such initiative, and the board wants to understand the business case for it. It also wants to see a clear plan to measure outcomes, including systems and data. Raymond knows that some of the board members are relatively new, that almost all of them are independent directors from outside the company.
Originally Published in: Cascio, W. (2009). Aetna: Investing in Diversity. Alexandria, VA: Society for Human Resource Management.
Description based on online resource; title from home page (viewed on May 4, 2016).
Keywords: elektronické knihy; electronic books; Diversity in the workplace -- Case studies